Overview of Blood Pressure After Spinal Anesthesia with Preload and Without Preload 20cc Ringer Lactate in The Operating Room - Dedi, Dedi Irawan; Sukmaningtyas, Wilis; Susanto, Amin (Global Indonesia Health Care (GOICARE), 2025)
Background: Spinal anesthesia is known to affect blood pressure by raising or lowering blood pressure levels, including MAP and pulse rate. While colloidal fluid therapy is indicated for the management of such variations, it remains longer in the intravascular space and supports blood pressure stabilization. Purpose: This study attempts to analyze the time and amount of Ringer Lactate fluid administration to stabilize blood pressure back to normal levels after spinal anesthesia. Methods: Quantitative research was adopted with an analytical, cross-sectional observation design. Data collection was facilitated using sheets for observing blood pressure and measuring blood pressure using a Tension meter. The study was performed over one month, from July to August, at Awal Bros Batam Hospital. A total of 40 respondents were taken for this study using total sampling. The data collected were analyzed using univariate analytical methods. Results: From the analysis, the mean average time taken for blood pressure changes after spinal anesthesia is 12.15 minutes standard deviation of 3.363. The time taken varied from a minimum of 5 minutes to a maximum of 20 minutes. As for the volume of Ringer Lactate fluid, on average, the volume given was 20 ccc/KGBB. Blood pressure change after spinal anesthesia had a mean of 99.65 standard deviations of 30.783, with the minimum measurement at 22 and the maximum at 167. Conclusion: This study shows the importance of giving Ringer Lactate fluid to stabilize blood pressure following spinal anesthesia, where both time and volume correlate positively with changes in blood pressure